Impact of Proactive Nurse Participation in ICU Family Conferences: A Mixed-Method Study. Issue 6 (June 2016) - Garrouste-Orgeas, Maité; Max, Adeline; Lerin, Talia; Grégoire, Charles; Ruckly, Stéphane; Kloeckner, Martin; Brochon, Sandie; Pichot, Emmanuelle; Simons, Clara; El-Mhadri, Myriame; Bruel, Cédric; Philippart, François; et al.
Abstract : Objectives: To investigate family perceptions of having a nurse participating in family conferences and to assess the psychologic well being of the same families after ICU discharge. Design: Mixed-method design with a qualitative study embedded in a single-center randomized study. Setting: Twelve-bed medical-surgical ICU in a 460-bed tertiary hospital. Subjects: One family member for each consecutive patient who received more than 48 hours of mechanical ventilation in the ICU. Intervention: Planned proactive participation of a nurse in family conferences led by a physician. In the control group, conferences were led by a physician without a nurse. Measurements and Main Results: Of the 172 eligible family members, 100 (60.2%) were randomized; among them, 88 underwent semistructured interviews at ICU discharge and 86 completed the Peritraumatic Dissociative Experiences Questionnaire at ICU discharge and then the Hospital Anxiety Depression Questionnaire and the Impact of Event Scale (for posttraumatic stress–related symptoms) 3 months later. The intervention and control groups were not significantly different regarding the prevalence of posttraumatic stress–related symptoms (52.3 vs 50%, respectively; p = 0.83). Anxiety and depression subscale scores were significantly lower in the intervention group. The qualitative data indicated that the families valued the principle of the conference itself. Perceptions of nurse participation clustered into four main themes: trust that ICU teamwork was effective (50/88; 56.8%), trust that care was centered on the patient (33/88; 37.5%), trust in effective dissemination of information (15/88; 17%), and trust that every effort was made to relieve anxiety in family members (12/88; 13.6%). Conclusions: Families valued the conferences themselves and valued the proactive participation of a nurse. These positive perceptions were associated with significant anxiety or depression subscale scores but not with changes in posttraumatic stress–related symptoms. Abstract : Supplemental Digital Content is available in the text.